Grace after genocide : Cambodians in the United States - Mortland, Carol A. (Carol Anne), 1945- (Berghahn, 2019)
"Grace after Genocide is the first comprehensive ethnography of Cambodian refugees, charting their struggle to transition from life in agrarian Cambodia to survival in post-industrial America, while maintaining their identities as Cambodians. The ethnography contrasts the lives of refugees who arrived in America after 1975, with their focus on Khmer traditions, values, and relations, with those of their children who, as descendants of the Khmer Rouge catastrophe, have struggled to become Americans in a society that defines them as different. The ethnography explores America's mid-twentieth century involvement in Southeast Asia and its enormous consequences on multiple generations of Khmer refugees"--